'SNO'-Storms Compromise Protein Activity and Mitochondrial Metabolism in Neurodegenerative Disorders. (December 2017) - Nakamura, Tomohiro; Lipton, Stuart A.
Abstract : The prevalence of neurodegenerative diseases, including Alzheimer's disease (AD) and Parkinson's disease (PD), is currently a major public health concern due to the lack of efficient disease-modifying therapeutic options. Recent evidence suggests that mitochondrial dysfunction and nitrosative/oxidative stress are key common mediators of pathogenesis. In this review, we highlight molecular mechanisms linking NO-dependent post-translational modifications, such as cysteine S-nitrosylation and tyrosine nitration, to abnormal mitochondrial metabolism. We further discuss the hypothesis that pathological levels of NO compromise brain energy metabolism via aberrant S-nitrosylation of key enzymes in the tricarboxylic acid (TCA) cycle and oxidative phosphorylation, contributing to neurodegenerative conditions. A better understanding of these pathophysiological events may provide a potential pathway for designing novel therapeutics to ameliorate neurodegenerative disorders. Trends: Neurons are particularly sensitive to dysfunction in mitochondrial metabolism due to their high energy demands. Excessive production of NO-related species is linked to mitochondrial metabolic defects in neurodegenerative diseases. Aberrant protein S-nitrosylation (producing SNO-proteins) mediates pathological NO signaling cascades, contributing to mitochondrial metabolic dysfunction. A wide range of aberrantly S-nitrosylated mitochondrial proteins that may contribute to neurodegenerative diseases has been identified; these SNO proteins include enzymes involved in the TCA cycle, the ETC, and mitochondrial dynamics. Aberrant S-nitrosylation of specific proteins may represent a key mediator of both T2DM/MetS and neurodegenerative disorders such as AD.